Hepatitis B and A virus antibodies in alcoholic steatosis and cirrhosis. Issue 7 (July 1982) - Gluud, C; Aldershvile, J; Henriksen, J; Kryger, P; Mathiesen, L
Abstract : Sera from 74 alcoholics with cirrhosis and 63 alcoholics with steatosis were tested for antibody to hepatitis B surface antigen, to hepatitis B core antigen, and to hepatitis A virus by radioimmunoassay or enzyme-linked immunosorbent assay. No significant difference between the two groups of alcoholics could be found concerning the prevalence of these antibodies. The total group of patients had antibody to hepatitis B surface antigen or hepatitis B core antigen, or both, significantly (p less than 0.001) more often (26%) than sex- and age-matched controls (4%). No significant difference was found between patients and controls concerning the prevalence of antibody to hepatitis A virus (46% v 40%). In patients with cirrhosis, no correlation between wedged hepatic vein pressure or wedged-to-free hepatic vein pressure and any of the viral antibodies could be established. The present results suggest that hepatitis B virus does not play a major role in the progression of alcoholic liver disease, but longitudinal studies are needed to solve this problem. The reason for the increased prevalence of antibodies to hepatitis B virus in these patients is unknown.